Is it Truly Easy for Second Language Learners to Compose -ing Form Construction? - Aziz, Muhammad Fahruddin; Triyono, Sulis (PAROLE: Journal of Linguistics and Education, 2017)
English rules are occasionally restricted, for instance, -ing form. This form is acquired in the early stage of natural acceptance and whether the earliest will guarantee ESL students to understand and compose it easily. This research is designated to investigate errors, sources of errors, and error tendencies made by students in composing –ing form. This research was carried out at UAD University in the English Department. Writing essay test was utilized to diagnose the tendency of –ing form misconception. Erroneous data were identified and categorized based on surface structure taxonomies and communication effect taxonomies. The findings prove that –ing form construction is not that easy for students to compose. Misformation frequenly appears due to some inappropriate formulation, mainly when students are asked to compose the –ing form as the constituent of phrase or clause, the direct object of certain verbs, and object of preposition with a particle of preposition to. The main factor affecting the deviation is caused by the distinct linguistic system of both English and Indonesian. The lack of knowledge towards the target language or incomplete instruction additionally makes students over-generalize every aspect of English rule which is occasionally restricted.